Direct Democracy and Minority Rights: Direct and Indirect Effects on Religious Minorities in Switzerland - Christmann, Anna (Politics and religion, 2012)
Most of the research on the effects of direct democracy on minority rights is empirically limited to the direct effects of direct democracy. This article takes the issue a step further and examines both direct and indirect effects by investigating the rights of religious minorities in Switzerland. The analysis provides two main insights: all direct effects are negative and can be observed when the rights of out-groups like Islamic minorities are at stake. Second, indirect effects on the parliamentary process can be observed, too: parliaments make laws more restrictive toward Islamic minorities if they fear a popular vote. However, they develop strategies to enforce their liberal interests, as shown by the fact that extensions of the rights of religious minorities are passed in total revisions.